RETRACTED: Matrine Protects Cardiomyocytes Against Hyperglycemic Stress by Promoting Mitofusin 2-Induced Mitochondrial Fusion - Xiao, Tong; Huang, Jie; Liu, Yuan; Zhao, Yujie; Wei, Manman (Frontiers in Physiology, 2021)
Matrine, an active component of Sophora flavescens Ait root extracts, has been used in China for years to treat cancer and viral hepatitis. In the present study, we explored the effects of matrine on hyperglycemia-treated cardiomyocytes. Cardiomyocyte function, oxidative stress, cellular viability and mitochondrial fusion were assessed through immunofluorescence, quantitative real-time PCR, enzyme-linked immunosorbent assays and RNA interference. Matrine treatment suppressed hyperglycemia-induced oxidative stress in cardiomyocytes by upregulating transcription of nuclear factor erythroid 2-like 2 and heme oxygenase-1. Matrine also improved cardiomyocyte contractile and relaxation function during hyperglycemia, and it reduced hyperglycemia-induced cardiomyocyte death by inhibiting mitochondrial apoptosis. Matrine treatment increased the transcription of mitochondrial fusion-related genes and thus attenuated the proportion of fragmented mitochondria in cardiomyocytes. Inhibiting mitochondrial fusion by knocking down mitofusin 2 abolished the cardioprotective effects of matrine during hyperglycemia. These results demonstrate that matrine could be an effective drug to alleviate hyperglycemia-induced cardiomyocyte damage by activating mitofusin 2-induced mitochondrial fusion.